Analisis Rhodamin-B pada Saos yang Beredar di Sekitar STIKes Bhakti Husada Mulia Madiun dengan Metode KLT dan Spektrofotometri UV-Vis - Mohamad Afif Ramadhi; Susanti Erikania; Yetti Hariningsih (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2021)
Sauce is a flavoring and flavor enhancer that is thick and red in color. The sauce is suspected to contain Rhodamine-B as coloring agent because a bright red color fluorescence. This study aims to analyze qualitatively and quantitatively Rhodamin-B in the sauce circulating around STIKes Bhakti Husada Mulia. This research method used 5 sauce samples, analyzed qualitatively by TLC using silica gel GF254 stationary phase and mobile phase n-butanol:ethyl.acetate:ammonia (10:4:5), and quantitatively analyzed by UV-Vis Spectrophotometry with maximum wavelength determination 400-800 nm ​​with concentration 3 ppm. The results of qualitative analysis by TLC showed that 4 of 5 positive samples containing Rhodamine-B appeared orange stains on a 254 nm UV lamp and yellow fluorescence on a 360nm UV lamp, while the Rf value in sample B was 0.57; sample C was 0.58; sample D was 0.58 and sample E was 0.58, compared to the Rhodamine-B standard of 0.55. The results of quantitative analysis UV-Vis spectrophotometry at maximum wavelength of 558nm with absorbance value 0.538 A, the Rhodamine-B content in sample B was 1.216μg/ml±0.004; sample C 2.278μg/ml±0.005; sample D 1.681μg/ ml±0.007 and sample E 0.776μg/ml±0.004. The conclusion is sample C has the highest levels of Rhodamine-B compared to samples B, D and E. Keywords: TLC, Rhodamine-B, Sauce, and UV-Vis Spectrophotometry